2021
DOI: 10.1111/jdv.17126
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnosis of secondary syphilis in a Rituximab‐treated patient: an emerging diagnostic challenge?

Abstract: missense mutation (rs201253322) in PASH syndrome 4 was also located in the same exon (c. 1213 C>T; p. Arg405Cys).Association testing of SNVs with Hurley staging and found that rs116895455 remained significant after adjustment for gender, smoking history and BMI (P = 0.018). rs116895455 is located in intron 12 of PSTPIP1, within a candidate cis-regulatory element. All patients with the heterozygous CG genotype (n = 4) were diagnosed with more severe disease, and three bore the A*24:02-B*54:01-C*01:02 haplotype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies reported mild COVID-19 even in the absence of a measurable anti-SARS-CoV-2 antibody response [56][57][58][59][60][61], highlighting that the antiviral T cell response may be important for clearing SARS-CoV-2 infection [62]. Another study reported that the syphilis antibody response was absent in a rituximab-treated patient [63], and loss of varicella-zoster virus antibodies was reported in a patient treated with ocrelizumab [64]. These findings have obvious clinical implications in patients treated with anti-CD20 antibodies.…”
Section: Immunological Effects Of Anti-cd20 Antibody Therapymentioning
confidence: 99%
“…Several studies reported mild COVID-19 even in the absence of a measurable anti-SARS-CoV-2 antibody response [56][57][58][59][60][61], highlighting that the antiviral T cell response may be important for clearing SARS-CoV-2 infection [62]. Another study reported that the syphilis antibody response was absent in a rituximab-treated patient [63], and loss of varicella-zoster virus antibodies was reported in a patient treated with ocrelizumab [64]. These findings have obvious clinical implications in patients treated with anti-CD20 antibodies.…”
Section: Immunological Effects Of Anti-cd20 Antibody Therapymentioning
confidence: 99%
“…Serological non-treponemal screening tests (VDRL, RPR ‒ Rapid Test Reagin) and confirmatory treponemal tests (FT-ABS, TPHA ‒ Treponema Pallidum Hemagglutination Assay, TPPA ‒ Treponema Pallidum Particle-Agglutination assay) are widely used for the diagnosis of syphilis, and the molecular PCR assay and immunohistochemistry should be considered in the investigation of atypical cases, or conditions in which the humoral response and serological tests may be impaired. 1 , 2 …”
mentioning
confidence: 99%
“…A previous report of a patient treated with rituximab for multiple sclerosis and skin eruption typical of secondary syphilis showed negative VDRL and TPPA serological tests on repeated measurements and delayed seroconversion for more than three weeks after the onset of symptoms and skin manifestations, but PCR and immunohistochemistry were positive for T. pallidum . 2 …”
mentioning
confidence: 99%